Female mate preference for egg-caring males in the giant water bug Diplonychus rusticus (Heteroptera Belostomatidae). Issue 5 (3rd September 2018) - Ohba, Shin-ya; Matsuo, Sayaka; Huynh, Thi T. Trang; Kudo, Shin-ichi
Abstract : Paternal care can be maintained under sexual selection in case that it helps caring males to attract more mates. Females of two back-brooding water bug species, the belostomatids Appasus major and A. japonicus, prefer egg-caring males over non-caring males. Here, we tested under laboratory and field conditions whether females of another belostomatid species, Diplonychus rusticus, prefer egg-caring males as mating partners. Caring males received more eggs from females than non-caring males under the both conditions. Our results suggest that sexual selection plays an important role in maintaining paternal care not only in species of the genus Appasus, but also in the genus Diplonychus .